Pelatihan Terpadu Smart Agroeduwisata: Inovasi Budidaya, Pengelolaan Limbah, dan Penguatan Kelembagaan Pemuda Di Desa Sukamaju - Wahid, Abdul; Patappari Firmansyah, Amanda; Zul Fariduddin Attar, A. Farmy; Basir, Basri (Pusat Pengembangan Pendidikan dan Bakat Indonesia/Education and Talent Development Center of Indonesia (ETDC Indonesia), 2025)
This community engagement program was conducted in Sukamaju Village, Tellu Limpoe Subdistrict, Sinjai Regency, with the primary goal of developing a local innovation ecosystem through the integration of dragon fruit cultivation technology, organic waste management, and youth institutional strengthening. The activity stemmed from several issues faced by the community, including suboptimal farm productivity, unutilized dragon fruit waste, and limited managerial capacity of the village youth organization (Karang Taruna) in business administration and product marketing. The training was designed to shift the community’s mindset from conventional farming toward sustainable agricultural practices with economic value. The implementation method consisted of three phases: preparation, execution, and mentoring. The program lasted for two months and applied a participatory approach involving 45 participants from the “Merpati” Farmers Group and Karang Taruna of Sukamaju Village. The training covered four main sessions: (1) dragon fruit cultivation technology using drip irrigation, LED grow lights, and biofertilizers; (2) waste processing into compost, silage, and natural extracts; (3) product design and brand development under the label “Sukamaju Organika”; and (4) organizational strengthening and digital business recordkeeping. Each session included field practice, coaching clinics, and pre–post evaluations to measure learning improvement and skill acquisition. The results revealed a 78% average increase in participants’ knowledge scores, with the highest improvement observed in the product design and branding session. Tangible outcomes included the establishment of a youth business unit under Karang Taruna utilizing digital bookkeeping systems and the ability to convert agricultural waste into value-added products. Beyond improving cultivation efficiency and waste management, the program fostered a spirit of social entrepreneurship among rural youth. This activity presents a significant advancement in community engagement models, where young villagers act as innovation agents in advancing sustainable smart agroedutourism.